Effect of Wavelength on Metrological Characteristics of Non-Holographic Fiber Specklegram Sensor (2015)
In this paper, we report some results about the effects of varying the wavelength in a structure of a non-holographic fiber specklegram sensor. In these arrangements, the speckle pattern produced by a multi-mode optical fiber is coupled to the asingle-mode optical fiber with lower numerical aperture, which produces a filtering effect that can be used as an optical transduction mechanism. The influence of the wavelength on the sensor performance is evaluated by changing the laser wavelength, and a strong effect on the linearity and reproducibility of its response is found. Lasers emitting at 1310 nm, 1550 nm, and 1625 nm are used.